The Russo-Ukrainian war and financial markets: the role of dependence on Russian commodities - Lo, Gaye-Del; Marcelin, Isaac; Bassène, Théophile; Sène, Babacar (Finance research letters, 2022)
•We study the influence of the Russo-Ukrainian war on financial markets, subject to a dependence on Russian commodities.•Results indicate a significant negative effect on major financial markets with a greater effect on volatility than on returns.•The effect of the war on returns is significant for countries with a dependence beyond the [0–20%] level, the threshold for an adverse effect on asset prices.•The military conflict exacerbates volatility regardless of dependence levels – the effect increases with dependence.•Developed markets are more affected than emerging markets and the effect increases with the dependence on Russian fuel commodities. This study examines the influence of the Russo-Ukrainian war on financial markets, conditioned upon a country's dependence on Russian commodities, employing a large panel of 73 countries. Financial markets reacted to the war-induced shock significantly, with a weaker effect on asset prices than volatility. Markets perceived the dependence on Russian commodities as a significant risk factor, sinking stock returns and intensifying instability. The effect of the war on returns was significant for countries with a dependence beyond the [0–20%] level, suggesting a threshold for an adverse effect on asset prices. The armed conflict exacerbated volatility regardless of dependence levels; the effect increased with dependence. Results have implications for diversification strategies in international exchanges.